Review of pharmacotherapy for smoking cessation in patients with schizophrenia - Shawen, Avery E. (Ment Health Clin, 2018)
Smoking cessation is a chronic issue surrounding individuals with schizophrenia. It is estimated that up to 90% of patients diagnosed with schizophrenia smoke cigarettes. The purpose of this article is to provide a nonsystematic review of the efficacy of smoking cessation interventions as well as to explore the potential neuropsychiatric adverse effects of these agents in patients with schizophrenia. Eighteen studies were found and included in the review. Overall, nicotine replacement therapy, bupropion, and varenicline have all proven their effectiveness at either promoting smoking abstinence or a significant reduction in cigarette use.